2020
DOI: 10.1016/j.jsps.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Sennoside A drug capped biogenic fabrication of silver nanoparticles and their antibacterial and antifungal activities

Abstract: Sennoside A (dianthrone glycoside) shows laxative properties and used as a folk traditional medicine. Sennoside A capped silver nanoparticles (Ag/sennoside A) were synthesized at room temperature for the first time by using sennoside A as reducing and capping agent. UV–visible spectroscopic data reveals that the absorption peaks of pure sennoside A was appeared at 266, and 340 nm, which red shifted to 304, and 354 nm at higher sennoside A concentration. Upon addition of the Ag + ions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 67 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…10 where η = viscosity of the solvent, D = dielectric constant of the solvent, and EM = electrophoretic mobility. The NPs with zeta potential more negative than −30 mV and more positive than +30 mV are stable [24]. The zeta potentials were found to be −8 mV and −30 mV, respectively, for DPE-and CTAB-AgNPs.…”
Section: Characterization Of Agnpsmentioning
confidence: 92%
See 1 more Smart Citation
“…10 where η = viscosity of the solvent, D = dielectric constant of the solvent, and EM = electrophoretic mobility. The NPs with zeta potential more negative than −30 mV and more positive than +30 mV are stable [24]. The zeta potentials were found to be −8 mV and −30 mV, respectively, for DPE-and CTAB-AgNPs.…”
Section: Characterization Of Agnpsmentioning
confidence: 92%
“…Transition metal NPs have been fabricated form various parts of natural plants such as leaf [13,14], fruit [15,16], stem [17], roots [18], flower [19] and others sustainable low cost and eco-friendly natural materials [20,21]. The bioorganic materials of natural resources acted as capping and reducing agent, which control aggregation and agglomerations of the NPs [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Plants have long been used in treating human wellness issues with therapeutic medication in multiple historical systems. The cosmetics, dairy, color, and pharmaceutical industries frequently employ natural plant extracts due to their potential medicinal and pharmaceutical applications [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that sennosides including SA (100–400 g/ml) had an inhibitory effect on a wide range of bacteria and fungi, such as Salmonella typhi , Staphylococcus aureus (S. aureus) , Pseudomonas aeruginosa , Escherichia coli (E. coli) , Streptococcus pneumoniae , Bacillus subtilis , Rhizoctonia bataticola , Fusarium moniliforme , Aspergillus niger , Aspergillus flavus , Candida albicans ( Ram Avtar Sharma, 2012 ). In addition, SA-capped silver nanoparticles (Ag/SA NPs), synthesized with SA as reducing and capping agent at room temperature, significantly inhibited two bacteria strains ( S. aureus and E. coli ) and two yeast strains ( Candida albicans and Candida parapsilosis ) ( Al-Ghamdi et al, 2020 ). Similarly, Ontong et al showed that AgNPs, made the extracts of senna leaf as reducing and capping agents, exhibit strong inhibitory effects against various Gram-positive or -negative bacteria and fungi, by impairing the microorganism morphology and membrane integrity ( Ontong et al, 2019 ).…”
Section: Pharmacologymentioning
confidence: 99%